Intracoronary artery retrograde thrombolysis combined with percutaneous coronary interventions for ST-segment elevation myocardial infarction complicated with diabetes mellitus: A case report and literature review - Shen, Mingzhi; Liao, Yichao; Wang, Jian; Zhou, Xinger; Guo, Yuting; Nong, Yingqiao; Guo, Yi; Lu, Haihui; Jin, Rongjie; Wang, Jihang; Fu, Zhenhong; Li, Dongyun; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background: The management of large thrombus burden in patients with acute myocardial infarction and diabetes is still a worldwide problem. Case presentation: A 74-year-old Chinese woman presented with ST-segment elevation myocardial infarction (STEMI) complicated with diabetes mellitus and hypertension. Angiography revealed massive thrombus formation in the mid-segment of the right coronary artery leading to vascular occlusion. The sheared balloon was placed far from the occlusion segment and urokinase (10WU) was administered for intracoronary artery retrograde thrombolysis, and TIMI grade 3 blood flow was restored within 7 minutes, and one stent was accurately implanted into the culprit vessel. No reflow, slow blood flow, or arrhythmia occurred during this process. Conclusion: Intracoronary artery retrograde thrombolysis can be effectively and safely used in STEMI patients with diabetes mellitus and hypertension, even if the myocardial infarction exceeds 12 hours. (REST or named ICART ClinicalTrials.gov number, ChiCTR1900023849)